2017
DOI: 10.1590/2359-3997000000308
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin levels before radioactive iodine therapy and dynamic risk stratification after 1 year in patients with differentiated thyroid cancer

Abstract: Objectives: We sought to assess the relationship between stimulated thyroglobulin (sTg) before radioactive iodine therapy (RIT), and the dynamic risk stratification 1 year after treatment, and to establish the utility of the sTg as a predictor of response to therapy in these patients. A retrospective chart review of patients with differentiated thyroid cancer (DTC) who underwent RIT after surgery and were followed for at least 1 year, was carried out. Subjects and methods: Patients were classified according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…Perhaps the reason for this difference between the results is due to the strict criteria used in the present study, in which only cases with excellent responses in the last assessment were classified as DF (5).The NDF group also had higher percentages of cases with detectable first STg. The prognostic value of STg, measured after TT and before RIT, both in the short and long term, has been reported by several authors (33,34). However, the groups classified according to the preoperative cytological class did not differ regarding this parameter, minimizing its influence on the evaluated outcomes.…”
Section: Thyroid Cancer: Cytology Versus Prognosismentioning
confidence: 60%
“…Perhaps the reason for this difference between the results is due to the strict criteria used in the present study, in which only cases with excellent responses in the last assessment were classified as DF (5).The NDF group also had higher percentages of cases with detectable first STg. The prognostic value of STg, measured after TT and before RIT, both in the short and long term, has been reported by several authors (33,34). However, the groups classified according to the preoperative cytological class did not differ regarding this parameter, minimizing its influence on the evaluated outcomes.…”
Section: Thyroid Cancer: Cytology Versus Prognosismentioning
confidence: 60%
“…The prognostic role of postoperative Tg has been studied in numerous publications [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]34]. Although the studies differed in the risk classification of patients and in the method of cut-off value selection, the authors found that the Tg value is an important prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Following surgery, Tg values are influenced by the mass of the remaining normal thyroid tissue and of the tumor, as well as the mode and duration of stimulation. Many research groups have studied the prognostic role of stimulated Tg after surgery and before RAI ablation [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Recently, the routine use of RAI treatment has become questionable, which has also raised the question of whether the stimulated Tg value can help in making decisions about the necessity of RAI treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [12] reported that the D0Tg ≥ 2 ng/mL group had 23% of recurrence while the D0Tg < 2 ng/mL group had only 2% of recurrence. Banderia et al [13] reported that the cutoff D0Tg to predict therapeutic response was 3.75 ng/mL. However, these studies showed different single cutoff D0Tg for categorizing high and low Tg levels to predict the therapeutic outcome following previous reports [14].…”
Section: Discussionmentioning
confidence: 99%